AN ANALYSIS OF IMAGERIES IN E.E. CUMMINGS’ SELECTED POEMS - Leni Tiwiyanti; Mu’thia Mubasyira (Pujangga: Jurnal Bahasa dan Sastra, 2020)
This research analyzes the imageries used by E.E. Cummings in two poems by E.E. Cumming. He is a 20th century poet and novelist known for his unique style and structure. He considered himself a painter as well as a poet. Most of his poems are free verse in which he innovates a new style of writing which disregard any traditional rules and regulations of writing. The purpose of this research is to identify the types of imageries used in some of selected poems by E.E. Cummings and how the imageries are applied in the poems. The method used is qualitative descriptive method. The source of the data are two poems “All in Green” and “Your Little Voice”. Imageries are used to make abstract ideas concrete and easier to communicate specially used in poems. From the analysis, there are only five types out of seven types of imageries found in both poems. The five types of of the imageries are visual, auditory, kinesthetic internal and gustatory imageries. Both techniques by description and figurative language are applied to build the imageries. There are nine imageries applied by using description technique and seven imageries with figurative language technique.Keywords: poems, imagery, types of imagery, technique in building imageryPenelitian ini menganalisis citraan yang digunakan oleh E. E. Cummings dalam beberapa karya puisinya. Dia adalah penyair dan penulis novel abad 20 yang dikenal dengan gaya dan struktur yang unik. Dia menilai dirinya sebagai seorang pelukis dan juga penyair. Dalam sebagian besar karyanya, dia menggunakan larik lepas yakni berinovasi dengan gaya menulis baru yang tidak megindahkan aturan atau ketentuan menulis tradisional. Tujuan dari penelitian untuk mengetahui jenis-jenis citraan puisi dan teknik yang digunakan untuk membangun dalam puisi karya E.E. Cummings. Sumber data diambil dari dua puisi berjudul “All in Green” and “Your Little Voice”. Citraan digunakan untuk membuat ide abstrak menjadi nyata dan lebih mudah dikomunikasikan terutama dalam puisi. Dari Analisis, hanya terdapat lima dari tujuh jenis citraan yang digunakan dalam kedua puisi. Kelima citraan tersebut adalah citraan penglihatan, citraan pendengaran, citraan gerak, citraan perasaan dan citraan pengecapan. Kedua teknik deskripsi dan bahasa kiasan digunakan dalam membangun cintraan. Terdapat 9 citraan menggunakan teknik deskripsi dan tujuh citraan mengunakan teknik bahasa kiasan.Keywords: puisi, citraan, tipe citraan, teknik membangun citraan